The Influence of Attitude, Subjective Norm, and Perceived Behavior Control on the Early Detection of Cervical Cancer among Female Students - Putri, Santy Irene (Journal of Maternal and Child Health, 2021)
Background: Cervical cancer is the fourth most frequent female malignancy in the globe, affecting an estimated 527,624 women every year and resulting in 265,672 deaths. This study aimed to determine the effect of attitudes, subjective norms, and perceived behavioral control on early detection of cervical cancer in female students. Subjects and Method: This was an analytic observational study with a cross-sectional approach. This study was conducted in Malang, East Java, Indonesia. The sample size of 350 female students was selected by simple random sampling technique. The dependent variable is the early detection of cervical cancer. The independent variables include attitudes, subjective norms, and perceived behavioral control. The data were collected by using a questionnaire and analysis using multiple linear regression. Results: Attitudes (b= 0.33; 95% CI= 0.22 to 0.44; p <0.001), subjective norms (b= 0.12; 95% CI= 0.01 to 0.22; p= 0.029), and perceived behavioral control (b= 0.32; 95% CI = 0.12 to 0.52; p= 0.002) has a relationship with behavior of early detection of cervical cancer in female students and statistically significant. Conclusion: Attitudes, subjective norms, and perceived behavioral control are factors that influence the behavior of early detection of cervical cancer in female students.